Volume 1: Codes and Standards 2005
DOI: 10.1115/pvp2005-71064
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mean Stress on the Fatigue Behavior of 304L SS in Air and PWR Water

Abstract: Load-controlled experiments on 304L stainless steel were run in Air and PWR water, at 150°C and 300°C, with and without a mean stress of 100MPa. These experiments were run to determine the influence of temperature, environment, and mean stress on the 107 Cycle Fatigue Limit stress amplitude. A 100MPa mean stress was found to have different effects at the different temperatures and environments. In contrast to all the conventional models used to describe the effects of mean stress, when the testing was done at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In general, the environmental effect can lower the fatigue limit, and the magnitude of the effect depends on the strain range. 10 This study is aimed at investigating the detailed strain range dependency of the environmental effect in simulated Nomenclature: ΔK ε , Strain intensity factor; Δε, Strain range; a, Crack depth; dε/dt, Strain rate; f, Geometrical constant for strain intensity factor; F en , Fatigue life correction factor; N f , Fatigue life; N f(air) , Fatigue life in air; N f(pred) , Fatigue life obtained by crack growth prediction; t, Thickness of hollow specimen; V air , Crack growth rate in air; V PWR , Crack growth rate in PWR water environment coolant water of a pressurized water reactor (PWR). It has been shown that the fatigue life consists of the number of cycles for small crack initiation (hereafter, initiation life) and that for the crack growing to a critical size for specimen failure (hereafter, growth life).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the environmental effect can lower the fatigue limit, and the magnitude of the effect depends on the strain range. 10 This study is aimed at investigating the detailed strain range dependency of the environmental effect in simulated Nomenclature: ΔK ε , Strain intensity factor; Δε, Strain range; a, Crack depth; dε/dt, Strain rate; f, Geometrical constant for strain intensity factor; F en , Fatigue life correction factor; N f , Fatigue life; N f(air) , Fatigue life in air; N f(pred) , Fatigue life obtained by crack growth prediction; t, Thickness of hollow specimen; V air , Crack growth rate in air; V PWR , Crack growth rate in PWR water environment coolant water of a pressurized water reactor (PWR). It has been shown that the fatigue life consists of the number of cycles for small crack initiation (hereafter, initiation life) and that for the crack growing to a critical size for specimen failure (hereafter, growth life).…”
Section: Introductionmentioning
confidence: 99%
“…As is seen, in the same loading condition, the fatigue life of the Z3CN20.09M ASS in water at 300 • C was shorter than that in air at RT [2,3,6,9,[13][14][15]. It indicates that the involvement of corrosive medium or the interactions of corrosive medium with applied load might be responsible for the decrease in the fatigue life of the Z3CN20.09M ASS [16,17]. At the same strain amplitude, the decrease in strain rate yielded a lower fatigue life [15,[18][19][20][21].…”
Section: Fatigue Lifementioning
confidence: 97%
“…Furthermore, the difference in the fatigue life at these three strain rates became more pronounced at higher strain amplitude. It might be caused by the higher corrosion rate of the tested material at higher strain amplitude in the autoclave environments [6,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Fatigue Lifementioning
confidence: 99%
“…The second method simply consists in multiplying the strain by a weighted K e value (K e avg ), defined as follows: (10) The analyst can choose either one of the methods or even use another methodology that ensures a conservative result.…”
Section: Evaluation Of the Environmental Factor For A Transient Pairmentioning
confidence: 99%